Black Monday, globalization and trading behavior of stock investors - Jeong-Ryeol Kurz-Kim (Deutsche Bundesbank, 2016)
Using a simple sign test, we report new empirical evidence, taken from both the US and the German stock markets, showing that trading behavior substantially changed around Black Monday in 1987. It turned out that before Black Monday investors behaved more as in the momentum strategy; and after Black Monday more as in the contrarian strategy. We argue that crashes, in general, themselves are merely a manifestation of uncertainty on stock markets and the high uncertainty due to globalization is mainly responsible for this change.
Keywords: C12; G02; G11; 330; Trading behavior; Momentum; Contrarian; Black Monday; Globalization; Uncertainty